Interpretation of Birrul Walidayn in Surah Al-Isra [17]: 24 (A Comparative Study of Tafsir Al-Azhar and Marah Labid) - Alimuddin, Muhammad Faqih; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
Devotion to both parents is a commendable trait often referred to as